Unpacking teacher candidates' decision-making and justifications in dilemmatic spaces during the student teaching year. Issue 3 (27th May 2018) - Ding, Ai-Chu; Wang, Hsiou-huai
ABSTRACT: Learning to teach is a complex process that hinges on teacher candidates' personal experiences, values, beliefs and characteristics, as well as the contexts they are exposed to. Student teaching as a transitional period may create dilemmas for teacher candidates, who are new to the profession and still learning about what it means to be a teacher. Thus, this study examined the dilemmas experienced by a group of Taiwanese teacher candidates during the student teaching phase. Using the framework of dilemmatic spaces, we identified the sources of their dilemmas and the decisions they made towards the dilemmatic situations and further examined how they justified their decisions. Our findings suggest that conflicting ideologies and teacher candidates' identities as student teachers are the main sources of their dilemmas. In response to the dilemmas, teacher candidates showed different decision-making trajectories that revealed the different actions and justifications they took within the dilemmatic space.